THE IMPLEMENTATION OF ISLAMIC EDUCATIONAL VALUES IN ADDRESSING THE PSYCHOLOGICAL IMPACT OF GADGET USE ON CHILDREN: A STUDY IN GAMPONG PEURADA - Cut Rizki Mustika; Murni; Rizki; Rusydi; Muhibuddin Hanafiah (Jurnal Ikhtibar Nusantara, 2026)
Advances in information technology have brought about significant changes in people’s lives, including for children who are becoming increasingly familiar with the use of gadgets. Uncontrolled use of gadgets can have various negative effects on children’s psychological development, such as a decline in social skills, emotional disturbances, addiction, and a reduced interest in learning. This study aims to analyse the internalisation of Islamic educational values as a means of addressing the psychological impact of gadget use on children in Gampong Peurada. The study employs a qualitative approach using field research methods. Data were collected through observation, interviews with parents, community leaders and religious figures, as well as documentation. The results of the study indicate that the internalisation of Islamic educational values is achieved through setting a good example, fostering a habit of worship, monitoring gadget use, family communication, and moral education from an early age. These efforts have a positive influence on character development, emotional control, and the social behaviour of children in using gadgets wisely.